Building cost comparison between conventional and formwork system: a case study of four-storey school buildings in Malaysia - Haron, Nuzul Azam; Hassim, Salihudin; Abdul Kadir, Mohd Razali; Jaafar, Mohd Saleh (Science Publications, 2005)
The Malaysian construction industry is undergoing a transitional change from an industry employing conventional technology to a more systematic and mechanized system. This new system is now known as the Industrialized Building System (IBS). This new method of construction can increase productivity and quality of work through the use of better construction machinery, equipment, materials and extensive pre-project planning. This study becomes very necessary since there is yet no organized body, which can provide the necessary information on the building cost comparison between the conventional system and industrialised building system in Malaysia's construction industry. This study also addresses the building cost comparison of the conventional system and industrialized building system of formwork system. It provides the details building cost between the conventional system and the formwork system and indicates which of the two is cheaper. The data were collected through questionnaire survey and case study, which consisting of institutional buildings. Through the statistical test 't-test' it is shown that there is a significant difference in cost saving for the conventional system as compared to the formwork system (industrialized building system).